Outer-membrane-acting peptides and lipid II-targeting antibiotics cooperatively kill Gram-negative pathogens - Qian Li (Nature Portfolio, 2021)
Li, Cebrian et al. show that a combination of peptide D-11 and vancomycin exhibits a potent antimicrobial activity against a panel of Gram-negative pathogens without apparent toxicity. They find that this combination is also effective in clearing Pseudomonas aeruginosa in mice, providing a potential antimicrobial therapy for humans.